THE ROLE OF "BERAKHLAK" WORK CULTURE IN IMPROVING EMPLOYEE PERFORMANCE WITH THE ADAPTABILITY AFTER POSITION EQUALIZATION AS A MEDIATION VARIABLE IN BONTANG CITY GOVERNMENT - Anton Dody Rushendra; Siti Maria; Ariesta Heksarini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Purpose: This study aims to analyze the role of BerAKHLAK work culture in accordance with the MENPAN-RB letter number 20 year 2021 on the employee performance with the adaptability after the equalization position from stuctrural to functional as a mediation variable within the Bontang City Government. Method: It is a quantitative research using a 5-point Likert scale questionnaire survey approach. A sample of 82 employees ASN who experienced equalization of positions was selected according to purposive sampling criteria. Data analysis using Structural Equation Modeling-Partial Least Square (SEM-PLS) with outer model, inner model, and bootstrapping testing. Result: The work culture did not have a big impact directly on performance (p-value 0.853), but it did have a big impact and significant effect on adaptability (p-value 0.001). Adaptability has a positive and significant effect on performance (p-value 0.000) and acts as a full mediator of the relationship between work culture and performance (p-value 0.000) with a contribution to explaining 81.3% of the variance in performance. Practical Implications for Economic Growth and Human Capital Development: Strengthening employee adaptation capacity with a training, coaching, mentoring, and a 360 degree feedback system is a key strategy for improving performance. This has an impact on the efficiency of public services, the optimization of professional human resources, the attractiveness of investment, and the growth of the MSME sector and creative industries in Bontang City as a partner area of the Ibu Kota Nusantara, the new capital city of Indonesia. Novelty: This study reveals the BerAKHLAK work culture does not have a direct impact on performance in the context of the Bontang City Government, because a strong local work culture has been embedded first (such as the slogan "extraordinary, professional, dignified"), so that adaptability is the only mechanism for channeling cultural influence on performance in the context of bureaucratic reform of equalization of positions.